Professional Development in Visual Arts - Linda Puppe; Helen Jossberger; Isabell Stein; Hans Gruber (Springer, 2022)
In the domain of visual arts, professional artists usually graduate from academies and universities. For professional development, art students must practise domain-specific activities. Support from lecturers and exchanges with fellow students also help advance accomplishments. Amateurs without academic or vocational artistic education can acquire their skills autodidactically or attend courses such as those at an adult-education centre. Empirical research in the domain of visual arts remains scarce; therefore, the present study’s objective was to analyse which kinds of domain-specific practice activities and social interactions artists, intermediates and amateurs rate as relevant to their artistic development in visual arts. The Professional Development in Arts Questionnaire (PDA-Q), including closed and open questions, was developed to examine artists’ activities and interactions. In this study, 81 experts, 58 intermediates and 31 amateurs participated. Experts and intermediates perceived domain-specific practice activities working on artworks and reflecting as the most important in their professional development. Experts and intermediates also rated these two activities as the most demanding. Amateurs rated these activities as less relevant and demanding. Experts and intermediates most often received feedback from lecturers and fellow students, while amateurs most often received feedback from friends and family. Experts and intermediates cited lecturers as being the most helpful sources of feedback, while amateurs cited family.